Pengaruh Mirror Therapyof The Face Terhadap Kemampuan Otot Wajah Pada Pasien Stroke di RSUD Kabupaten Kediri - Hanifah Auliya; Farida Hayati; Diana Rachmania (STIKES Karya Husada Kediri, 2018)
Stroke is the highest cause of death in Indonesia. Stroke is a potential abnormality in the brain's blood supply that causes disability, limb paralysis, speech disorders, thought processes due to brain function disorders and facial muscle disorders experienced by nerve (VII) facials. Therapy that can be done is ai mirror therapy exercise is a form of exercise to train shadow patients to improve the ability of facial muscles of stroke patients. The purpose of this study was to determine the effect of mirror exercise therapy on the ability of facial muscles in stroke patients in Kediri District Hospital. This study uses a pre-experimental design (one group pre test_post test), the sampling technique used was accidental sampling. The results showed that before mirror therapy all respondents (100%) criteria for the score range 25-36 and after doing mirror therapy all respondents (100%) criteria for the score range of 25-36. Data analysis showed (the value of P = 0.026 <α = 0.05) there was the effect of mirror therapy exercises on the ability of facial muscles in stroke patients in Kediri District Hospital. With meal mirror therapy, facial muscle disorders can be minimized by the effects of the Mirror Neuron system that can be used for lateral reconstruction, namely the ability to distinguish between the left and the right side It is recommended for Stoke patients to do mirror therapy as a form of exercise to improve the ability of sufferers' facial muscles stroke